Pancasila as the Sole Basis for all Political Parties and for all Mass Organizations: An Account of Muslims’ Responses - Ismail, Faisal (Studia Islamika, 1996)
One of the important policy of the New Order government in the political modernization process was the introduction of Pancasila as the sole foundation for social organizations and politics in Indonesia. Policies established in 1985, is the beginning of the fading aspirarsi basis of political legitimacy-oriented civic religion. Although this policy ultimately gained remarkable success, does not mean religious people in Indonesia accept it without facing a serious crisis-crisis. It can be seen from the response at least religious people who were forced to perform a review of the legitimacy of the social and political life.DOI: 10.15408/sdi.v3i4.778